Pengaruh Premi, Kualitas Pelayanan dan Klam terhadap Keputusan Memilih Produk Asuransi Jiwa Syariah di PT Bumiputera Cabang Iskandar Muda Medan - Siregar, Aristo Zaky Zein; Anggraini, Tuti; Inayah, Nurul (JIKEM: Jurnal Ilmu Komputer, Ekonomi dan Manajemen, 2022)
This study aims to: (1)Determine the effect of premiums on decisions customers in choosing sharia life insurance products PT.Bumiputera branch office Iskandar Muda Medan;  (2)Knowing the effect of service quality on customer decisions in choosing sharia life insurance products PT.Bumiputera branch office Iskandar Muda Medan; (3)Knowing the effect of claims on customer decisions in choosing products sharia life insurance PT.Bumiputera branch office Iskandar Muda Medan; (4)Know How do premiums, service quality and claims affect customer decisions? in choosing sharia life insurance products PT.Bumiputera branch office Iskandar Muda Medan.  The method used in this study is a quantitative method.  Sample used in this study amounted to 83 customers.  And using primary data by distributing questionnaires to customers and multiple regression analysis methods by using hypothesis testing.  The results of this study indicate that: (1)The premium variable partially has a significant positive effect on the decision customers in choosing sharia life insurance products; (2)Service quality variables partially does not have a significant positive effect on customer decisions in choosing sharia life insurance products; (3)The claim variable partially has an effect significantly positive on customer decisions in choosing life insurance products sharia; (4)The variables of premium, service quality and claims simultaneously have an effect on customer decisions in choosing sharia life insurance products.